An effective interferon‐gamma‐mediated inhibition of hepatitis C virus replication by natural killer cells is associated with spontaneous clearance of acute hepatitis C in human immunodeficiency virus‐positive patients. Issue 3 (21st January 2014) - Kokordelis, Pavlos; Krämer, Benjamin; Körner, Christian; Boesecke, Christoph; Voigt, Esther; Ingiliz, Patrick; Glässner, Andreas; Eisenhardt, Marianne; Wolter, Franziska; Kaczmarek, Dominik; Nischalke, Hans Dieter; Rockstroh, Jürgen K.; et al.
<x xml:space="preserve">Abstract</x> Hepatitis C virus (HCV) coinfection is an increasing health problem in human immunodeficiency virus‐positive (HIV+) individuals. However, a considerable proportion of HIV+ patients manage to overcome acute hepatitis C (AHC) spontaneously. In the present study, we analyzed the role of natural killer (NK) cells in modulating the course of AHC in HIV+ patients. Twenty‐seven HIV+ patients with AHC (self‐limited course: n = 10; chronic course: n = 17), 12 HIV+ patients with chronic hepatitis C (CHC), 8 HIV monoinfected individuals, and 12 healthy controls were studied. NK cells were phenotypically analyzed by flow cytometry. Interferon‐gamma (IFN‐γ) secretion, degranulation (CD107a), and anti‐HCV (= inhibition of HCV replication) activity of NK subpopulations were analyzed using the HuH7A2HCVreplicon cell system. NK cell frequency did not differ significantly between HIV+ patients with chronic and self‐limited course of AHC. However, we found NK cells from patients with self‐limiting infection to be significantly more effective in inhibiting HCV replication in vitro than NK cells from patients developing CHC. Of note, antiviral NK cell activity showed no significant correlation with NK cell degranulation, but was positively correlated with IFN‐γ secretion, and blocking experiments confirmed an important role for IFN‐γ in NK cell‐mediated inhibition of HCV replication. Accordingly, NK cells from patients that spontaneously cleared the virus displayed a stronger IFN‐γ secretion than those developing chronic infection. Finally, we observed high expression of NKG2D and NKp46, respectively, to be associated with self‐limiting course of aHCV. Accordingly, we found that blocking of these NK cell receptors significantly impaired antiviral NK cell activity. Conclusion: Our data suggest a strong IFN‐γ‐mediated antiviral NK cell response to be associated with a self‐limited course of AHC in HIV+ patients. (Hepatology 2014;59:814–827)